Case report: Early thrombosis in left atrial during transcatheter closure of ASD in a child with favorable outcome after use of GPIIb/IIIa receptor antagonist and heparin - Wang, Hui; Zhu, Zhiwei; Liu, Zhenyu; Yuan, Yonghua; Xu, Xuan; Liu, Liping; Wen, Jie; Xia, Xiaohui; Zhang, Yu; He, Jin (Frontiers in Pediatrics, 2023)
Background: Acute thrombus in atrial septal defect occluders is a rare complication that requires aggressive, effective, and safe management. Tirofiban, a platelet glycoprotein IIb/IIIa receptor antagonist, is commonly used in treating thromboembolic diseases, coronary heart disease, and stroke, yet, to date, no case of acute thrombosis after transcatheter closure of ASD children treated with tirofiban has been reported. Case Presentation: Herein, we reported a case of a 5-year-old girl with ASD who presented with acute thrombus on the left disc surface of the occluder device immediately after transcatheter closure of ASD. The thrombus was successfully dissolved 24 hours after a combined infusion of heparin and tirofiban, followed by 3 months of aspirin and clopidogrel and 3 months of aspirin alone. No thromboembolism or hemorrhage events occurred during follow-up for more than 2 years. Conclusion: The continuous infusion of platelet glycoprotein IIb/IIIa receptor antagonist tirofiban combined with heparin could dissolve thrombosis, avoiding the occurrence of embolism and reoperation.